Sapwood and Heartwood Contents on the Logs and Sawn Boards of Manglid (Manglieta glauca Bl.) - Mohamad Siarudin; Ary Widiyanto (Masyarakat Peneliti Kayu Indonesia, 2012)
The aim of this research is to identify the characteristics of sapwood and heartwood of manglid wood both in the logs and sawn boards; and to evaluate the differences of sapwood and heartwood content of sawn board from two sawing patterns: live sawing pattern and semi quarter sawing pattern. Totally 30 manglid logs coming from private forest in Sodonghilir sub-District, Tasikmalaya Regency were used as samples. About 35 sawn boards from each of sawing pattern were randomly chosen as specimens for sawn board observation. Result shows that manglid wood has thicker heartwood content than the sapwood on the log cross section, with the average of the heartwood and sapwood thickness is 17.04 and 6.57 cm, respectively. The thickness of heartwood part is positively correlated with the log diameter. Meanwhile, the percentage of the heartwood volume increases but the percentage of the sapwood decreases by the increasing of the log diameter. The higher thickness of the heartwood part compared to the sapwood part is consistent in the case of sawn board both from live sawing pattern and semi quarter pattern. Sawn board from the live sawing pattern has a lower sapwood percentage than the heartwood percentage on the width section.Key words: heartwood, live sawing, log, sapwood, semi quarter sawing